The effect of community nurse on mortality and hospitalization in a group of over-75 older adults: a nested case-control study - Terraciano, E.; Gentili, S.; Madaro, O.; Curti, E.; Inzerilli, M. C.; Albanese, L.; Accarino, N.; Tardi, A.; Orlando, S.; Riccardi, F.; Palombi, L.; Marazzi, M. C.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Bio-psycho-social frailty can negatively affect the health status of an ageing population. The integration between community nurses and social services can emphasize community care and prevent the onset of both health and social negative outcomes in the older population. The aim of the paper is to explore the causal association through the analysis of the hospitalization and mortality rate after a pro-active social service integrated by the community nurse.Study Design. A nested case-control study comparing groups of older adults has been carried out. Methods. The paper compares data stem from a cohort followed up by the University of Rome “Tor Vergata” with data from the “Long Live the Elderly!” program (LLE) cohort.Results. One-year standardized mortality rate was 6.5%, 4.7% and 7.5% in the control group, the LLE group and the LLE group integrated by the community nurse (LLE-CN), respectively. One-year hospitalization rate was 15.4%, 15.5% and 10.8% in the control group, the LLE group and the LLE-CN group, respectively. Conclusions. According to our results a social service with a pro-active approach, integrated by the community nurse, appears to be able to reduce mortality and hospitalization in a group of older adults aged>75. The multidimensional assessment of frailty stands for the first step of a new organization of community services.